The Haymarket Conspiracy : Transatlantic Anarchist Networks - Messer-Kruse, Timothy (Book collections on Project MUSE., 2012)
The Haymarket Conspiracy: Transatlantic Anarchist Networks traces the evolution of revolutionary anarchist ideas in Europe and their migration to the United States in the 1880s. A new history of the transatlantic origins of American anarchism, this study thoroughly debunks the dominant narrative through which most historians interpret the Haymarket Bombing and Trial of 1886-87._x000B__x000B_Challenging the view that there was no evidence connecting the eight convicted workers to the bomb throwing at the Haymarket rally, Timothy Messer-Kruse examines police investigations and trial proceedings that reveal the hidden transatlantic networks, the violent subculture, and the misunderstood beliefs of Gilded Age anarchists. Messer-Kruse documents how, in the 1880s, radicals on both sides of the Atlantic came to celebrate armed struggle as the one true way forward and began to prepare seriously for conflict. Within this milieu, he suggests the possibility of a "Haymarket conspiracy": a coordinated plan of attack in which the oft-martyred Haymarket radicals in fact posed a real threat to public order and safety. Drawing on new, never-before published historical evidence, The Haymarket Conspiracy provides a new means of understanding the revolutionary anarchist movement on its own terms rather than in the romantic ways in which its agents have been eulogized.